Pengaruh Sikap, Norma Subyektif, Kontrol Keperilakuan dan Kepercayaan Nasabah terhadap Niat Membeli Kembali Polis Asuransi Kerugian (Studi pada PT Asuransi Jasa Indonesia (Persero) Cabang Surabaya Korporasi) - Yudha, Eka Chandradi; Rohman, Fatchur; Sumiati, . (Universitas Brawijaya, Indonesia, 2015)
This study aims to determine whether attitude, subjective norm, behavioral control,and trust affect the intention to repurchase in general insurance policy. This researchwas conducted at PT Asuransi Jasa Indonesia (Persero) Surabaya Corporation Branch.This study was collected the data by using purposive sampling technique with certain conditions.This study uses multiple regression linear analysis. The findings of this study indicatethat attitudes, subjective norms, behavioral control and trust affect the intention torepurchase in general insurance policy. Trust is the most dominant variable in influencingintention to repurchase general insurance policy. The results of this research prove that trustis a key variable that can form intends customer confidence to repurchase.